RETRACTED: Activated Carbons From Winemaking Biowastes for Electrochemical Double-Layer Capacitors - Alcaraz, Lorena; Adán-Más, Alberto; Arévalo-Cid, Pablo; Montemor, Maria de Fatima; López, Félix A. (Frontiers in Chemistry, 2020)
Revalorizing organic biowaste is critical to achieve a full circular economy, where waste is transformed into resources. One of the main strategies is to produce activated carbons (ACs) and use them as functional materials for electrochemical energy storage. In this study, winemaking wastes, bagasse (BAG) and cluster stalks (CS), were recovered and used in the preparation of activated carbons by a hydrothermal process. Then, they were chemically activated using KOH and investigated for electrochemical capacitor applications. The activation treatment resulted in microporous structures, characterized by a Type I isotherm for low partial pressures (P/P0), and a Type IV for higher pressures, as observed by BET surface analysis, with specific surfaces of 1861 m2•g-1 and 2662 m2•g-1 for BAG and CS, respectively. These microporous structures were also investigated by means of scanning electron microscopy (SEM), revealing a high porous degree. Micro-Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) measurements displayed bands associated to disorder of the structure of the carbonaceous material. The electrochemical performance of the resulting materials was investigated for electrochemical energy storage applications, as supercapacitor electrode, in 1 M KOH aqueous electrolyte. These biowaste-derived materials displayed electrochemical double-layer capacitance, with 129 F•g-1 at 10 A•g-1 in the 0.1 V to -1.0 V vs. SCE. For that reason, they are pin-pointed as potential negative electrodes for electrochemical double-layer supercapacitors and hybrid or asymmetric supercapacitors.